Cannabis effects on driving longitudinal control with and without alcohol. Issue 11 (18th February 2016) - Hartman, Rebecca L.; Brown, Timothy L.; Milavetz, Gary; Spurgin, Andrew; Pierce, Russell S.; Gorelick, David A.; Gaffney, Gary; Huestis, Marilyn A.
Abstract: Although evidence suggests cannabis impairs driving, its driving‐performance effects are not fully characterized. We aimed to establish cannabis' effects on driving longitudinal control (with and without alcohol, drivers' most common drug combination) relative to psychoactive ∆ 9 ‐tetrahydrocannabinol (THC) blood concentrations. Current occasional (≥1×/last 3 months, ≤3 days per week) cannabis smokers drank placebo or low‐dose alcohol, and inhaled 500 mg placebo, low (2.9%), or high (6.7%) THC vaporized cannabis over 10 min ad libitum in separate sessions (within‐subject, six conditions). Participants drove (National Advanced Driving Simulator, University of Iowa) simulated drives 0.5–1.3 h post‐inhalation. Blood and breath alcohol samples were collected before (0.17 and 0.42 h) and after (1.4 and 2.3 h) driving. We evaluated the mean speed (relative to limit), standard deviation (SD) of speed, percent time spent >10% above/below the speed limit (percent speed high/percent speed low), longitudinal acceleration, and ability to maintain headway relative to a lead vehicle (headway maintenance) against blood THC and breath alcohol concentrations (BrAC). In N =18 completing drivers, THC was associated with a decreased mean speed, increased percent speed low and increased mean following distance during headway maintenance. BrAC was associated with increased SD speed and increased percent speed high, whereas THC was not. Neither was associated with altered longitudinal acceleration. A less‐than‐additive THC*BrAC interaction was detected in percent speed high (considering only non‐zero data and excluding an outlying drive event), suggesting cannabis mitigated drivers' tendency to drive faster with alcohol. Cannabis was associated with slower driving and greater headway, suggesting a possible awareness of impairment and attempt to compensate. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Cannabis' effects with/without alcohol on driving longitudinal control were evaluated against blood ∆ 9 ‐tetrahydrocannabinol (THC) and breath alcohol concentrations (BrAC) in 18 drivers at the National Advanced Driving Simulator, University of Iowa. THC was associated with decreased speed, increased driving time >10% below the speed limit, and increased following distance during headway maintenance; BrAC, with increased standard deviation (SD) speed and increased time >10% above the speed limit. Cannabis' association with slower driving and greater headway may suggest awareness of impairment, attempt to compensate.